PENERAPAN MODEL PEMBELAJARAN KOOPERATIF ACTIVE KNOWLEDGE SHARING UNTUK MENGETAHUI KETUNTASAN BELAJAR SISWA PADAPOKOK BAHASAN LAJU REAKSI DI SMA N 1 GUNUNG TOAR KAB. KUANTAN SINGINGI - Mira laswita; Betty Holiwarni; Elva Yasmi Amran (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract : Research implementation of cooperative learning model of active knowledge sharing aims to achieve mastery learning students on the subject of the reaction rate in class XI state senior high school 1 Gunung toar. his study uses a case study desihn one shot-study case. Time date retrieval from the 1st of November to 17 november 2014. The population is class XI science senior high school 1 gunung toar which consists of one class. The sample is total sample consisting of 1 class. Date were analyzed using classical learning completeness percentage calculation. Data retrieval technique is a technique test. Results of the research showed classical learning completeness 89,29% student attitudes 100% and skills of the students major domains 100%. Concluded that the implementation of cooperative learning model of active knowledge sharing can achieve mastery learning students on the subject of the rate of reaction in class XI state senior high school 1 gunung toar Regency kuantan singingi.Keywords : Kooperatif Active Knowledge Shring, Mastery Learning, Reaction Rate.